Efektivitas Penerapan Pojok Baca Dalam Peningkatan Literasi Peserta Didik Di SMPN 7 Kota Serang - Ria Yuni Lestari; Tati Rohmayati; Risti Oktaviani; Najiatul Karimah; Tiara Roudotul; Bilqis Suci Arfani Husnul Hotimah; Syahrul Syahrul (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The aim of this research is to determine and describe the effectiveness of implementing reading corners in increasing student literacy at SMP Negeri 7 Serang City. The implementation of this reading corner is one way to increase the literacy movement, in this case the literacy movement aims to motivate and familiarize students with reading and writing. This research uses a descriptive qualitative method with the research object of the reading corner at SMP Negeri 7 Serang City and the research subject. are teachers and also students at SMP Negeri 7 Serang City, and the data collection techniques used in this research are observation, interviews and documentation. The data obtained qualitatively shows that the reading corner at SMP Negeri 7 Serang City is able to increase literacy. The results of this research show that the reading corner has benefits: the school literacy report card has increased by 2% from 78% to 80%. , students become more confident, there is pleasure in students, students become familiar with various books, students are enthusiastic about the reading corner program, enthusiastic, find it easier to get the books they want to read, and are motivated.